Prioritising Alternative Solutions to Power Generation Problems Using MCDM Techniques: Nigeria as Case Study - Emovon, Ikuobase; Samuel, Olusegun David (International Journal of Integrated Engineering, 2017)
The engine that energizes industrialization and which invariably result to improved standard of living of nationsâ€™ citizens is electric power. Hence a steady power supply is crucial for Nigeria to achieve her aim of becoming one of the most industrialised nation in the world. However the biggest challenge in Nigeria is electricity crisis, a crisis that had been without any visible end in sight. From the literature the problems of power generation in Nigeria ranges from improper maintenance of power generation infrastructure to militant activities. Although alternative solutions are available for addressing these problems but there is difficulty in selecting the optimal solution that will yield greater power output. This paper present a Multi-Criteria Decision Making (MCDM) tool for prioritising alternatives solutions to power generation problems. The tool uses a combination of entropy technique and Multi-Attribute Utility Theory (MAUT) method. To illustrate the suitability of the technique, two examples were utilised. Results of the analysis revealed that Reliability Centered Maintenance (RCM) and diplomatic approach are the optimal solutions for resolving problem of improper maintenance and militant activities respectively. The proposed tool will assist Government or electric power managers to use optimal solutions in solving power generation problems in order to maximise power plant output and consistently ameliorate power crisis.Â